Vidia and the fairy crown - Driscoll, Laura; Clarke, Judith (New York : Random House Children's Books, 2006)
When Vidia, a disagreeable fairy, finds herself accused of stealing the Queen's tiara, she enlists the aid of a fellow sprite to help investigate and the two race against time to clear Vidia's name
"A Stepping Stone book."
Keywords: Fairies -- Fiction; Stealing -- Fiction; Lost and found possessions -- Fiction